2013
DOI: 10.3389/fendo.2013.00015
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin: Central and Peripheral Implications in Anorexia Nervosa

Abstract: Increasing clinical and therapeutic interest in the neurobiology of eating disorders reflects their dramatic impact on health. Chronic food restriction resulting in severe weight loss is a major symptom described in restrictive anorexia nervosa (AN) patients, and they also suffer from metabolic disturbances, infertility, osteopenia, and osteoporosis. Restrictive AN, mostly observed in young women, is the third largest cause of chronic illness in teenagers of industrialized countries. From a neurobiological per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 397 publications
2
29
0
1
Order By: Relevance
“…Ghrelin can cross the blood-brain barrier and act bidirectionally in the periphery and in the brain. In addition to its well-known role as a regulator of energy balance and food intake, Ghrelin may be involved in several brain mechanisms (Méquinion et al, 2013), many of those are altered in mood disorders as circadian rhythms (Kluge et al, 2013) and neuroinflammation (Miyake and Yamamura, 2009;Beynon et al, 2013). All these evidences indicated that an imbalance in Glucagon, GLP-1, GIP and Ghrelin levels might play a role in the pathogenesis of BD and in the mechanism causing the comorbidity between mood and metabolic disorders (Czepielewski et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Ghrelin can cross the blood-brain barrier and act bidirectionally in the periphery and in the brain. In addition to its well-known role as a regulator of energy balance and food intake, Ghrelin may be involved in several brain mechanisms (Méquinion et al, 2013), many of those are altered in mood disorders as circadian rhythms (Kluge et al, 2013) and neuroinflammation (Miyake and Yamamura, 2009;Beynon et al, 2013). All these evidences indicated that an imbalance in Glucagon, GLP-1, GIP and Ghrelin levels might play a role in the pathogenesis of BD and in the mechanism causing the comorbidity between mood and metabolic disorders (Czepielewski et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Insight into the modification of the endogenous ghrelin system seems to be promising not only for the control of obesity, but also for the management of clinically significant anorexia and pathological weight reduction. Accumulating evidence has shown that in patients with anorexia nervosa, there is a paradoxical increase in plasma ghrelin level even when compared with matched controls or obese patients (26), suggesting that there might be an insensitivity to ghrelin (27). Moreover, in vitro studies have documented that intra-peritoneal or systemic administration of ghrelin has the potential to improve the appetite and the nutritional status, and at the same time reduce the metabolic rate in patients with end-stage cancer (5).…”
Section: Ghrelin and Anorexiamentioning
confidence: 99%
“…Among the neuroendocrine systems controlling human appetite, studies of active AN have consistently implicated elevated ghrelin in the pathophysiology of abnormal appetite in this disorder (e.g., see Prince et al, 2009; Ogiso et al, 2011; Yi et al, 2011; Mequinion et al, 2013). Ghrelin is a potent orexigenic peptide, with levels rising sharply just before meals and falling to nadir within an hour after eating (Cummings et al, 2001; Shiiya et al, 2002).…”
Section: Introductionmentioning
confidence: 99%